ANALISIS PENGARUH KURS USD, HARGA BATUBARA ACUAN, DAN VOLUME PRODUKSI TERHADAP VOLUME EKSPOR PADA PT. BUKIT ASAM (PERSERO) TBK. - Theresia Anindita; ari apri syaputra (Politeknik APP Jakarta, 2017)
The research method used is descriptive quantitative. The data used are the USD exchange rate, coal price index, production volume, and export volume of 2014-2016 which is converted in monthly form, it is expected that this research will be utilized by the company to consider export sales and further research. The result of research based on multiple linear regression analysis showed that R2 equal to 16,3% which mean influence of USD exchange rate, coal price index and production volume to export volume only had effect of 16,3%. Partially only reference coal price index variable which significantly have positive effect. In simultaneously, the independent variable does not significantly affect the dependent variable.